Spinal fracture and luxation in dogs and cats - Bruce, C. W.; Brisson, B. A.; Gyselinck, K. (Veterinary and Comparative Orthopaedics and Traumatology, 2008)
The purpose of this retrospective study was to review cases of spinal fractures or luxations (SFL) treated with various modalities in order to describe fracture location, neurological status, treatment, outcome and complications in a patient population at a single centre. Medical records of dogs and cats diagnosed with a SFL between C1 and L7 between January 1995 and June 2005 were reviewed to collect pertinent data. Ninety-five cases were included in this study. Severity of spinal cord injury was graded on a scale from 0 to 5. Vehicular trauma was the most common cause of SFL. Spinal fractures were localized between C1-C5 in 10 cases, C6-T2 in 1 case, T3-L3 in 54 cases, L4-L7 in 36 cases. Thirty patients euthanized without treatment had a median neurological score of 5. Twenty-eight patients, all of which had motor function, were treated conservatively and there was not any change in their median neurological grade at the time of discharge.. Thirty-seven patients had surgery, 27 of which were non ambulatory. Thirty-five of 37 were stabilized using pins and/or screws and PMMA or various other techniques. The median neurological grade of surgically treated patients improved by one point between the time of initial diagnosis and discharge. Implant removal was performed in 5 cases. Patients treated with pins and/or screws and PMMA were significantly more improved than conservatively managed patients at the time of discharge, although the surgically treated patients were hospitalized significantly longer than conservatively managed patients. Our results suggest that dogs that retain pain sensation prior to surgery have a good prognosis for functional recovery. In this study, dogs that were treated conservatively retained purposeful movement and had a good prognosis for recovery.
Keywords: Spinal; fracture; luxation; dog; Cat